2014
DOI: 10.1080/07391102.2014.969772
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise development of structure–activity relationship of diverse PARP-1 inhibitors through comparative and validatedin silico modeling techniques and molecular dynamics simulation

Abstract: Inhibitors of poly (ADP-ribose) polymerase-1 (PARP-1) enzyme are useful for the treatment of various diseases including cancer. Comparative in silico studies were performed on different ligand-based (2D-QSAR, Kernel-based partial least square (KPLS) analysis, Pharmacophore Search Engine (PHASE) pharmacophore mapping), and structure-based (molecular docking, MM-GBSA analyses, Gaussian-based 3D-QSAR analyses on docked poses) modeling techniques to explore the structure-activity relationship of a diverse set of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Currently, increased expression of PARP-1 has been observed in multiple malignant types of tumor, including human osteosarcoma cells (20). As PARP-1 participates in DNA damage repair, the single application of a PARP-1 inhibitor treatment or a DNA damage drug combination may promote apoptosis (21). A previous study has demonstrated that drug inhibition or gene knockout PARP-1 may not only cause the avoidance of tissue damage caused by oxidative stress, but may also improve the prognosis of patients with cancer (22).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, increased expression of PARP-1 has been observed in multiple malignant types of tumor, including human osteosarcoma cells (20). As PARP-1 participates in DNA damage repair, the single application of a PARP-1 inhibitor treatment or a DNA damage drug combination may promote apoptosis (21). A previous study has demonstrated that drug inhibition or gene knockout PARP-1 may not only cause the avoidance of tissue damage caused by oxidative stress, but may also improve the prognosis of patients with cancer (22).…”
Section: Discussionmentioning
confidence: 99%
“…Computational approaches have also been employed. Novel inhibitor scaffolds have been revealed by strategies including docking, active-site fingerprinting, and molecular dynamics (MD) simulations incorporating pharmacophore modeling to account for the dynamics of the potential inhibitors in the binding site (629)(630)(631)(632)(633)(634). There are also new inhibitor therapies for use as single or combination therapy being developed by both synthesis and modification of existing inhibitors (635).…”
Section: Inhibitor Classesmentioning
confidence: 99%
“…Previous works on PARP‐1 MD simulations reported the involvement of polar interactions (hydrogen bonding and pi‐cation) and non‐polar interaction (Pi‐stacking) playing crucial roles in the higher activity of ligands in the active site of PARP‐1. Also, previous works described the involvement of van der Waals and hydrophobic interactions in the ligand‐PARP‐1 activities [11,17–19] . Findings from the current study may provide useful insights for the future rational design of novel PARP‐1 inhibitors for the treatment of cancer disease.…”
Section: Introductionmentioning
confidence: 59%
“…The poly (ADP) ribose polymers recruit other enzymes required for the repair of DNA. The indispensable role of PARP‐1 in the repair of single‐strand DNA lesions has made PARP‐1 a target in anticancer therapy [11] . Inhibitors of PARP‐1 are promising candidates for anticancer treatments [12] .…”
Section: Introductionmentioning
confidence: 99%